Cantharidin-Based Small Molecules as Potential Therapeutic Agents (2013)
Chemical and pharmacological information on cantharidin-based small molecules was analyzed. The review summarizes new facts about blister beetles’ metabolites for the period 2006–2012. General synthetic approaches to cantharidin-based small molecules as well as their chemical transformations and biological activities related to cantharidin, norcantharidin, cantharidimide, and norcantharimide analogs, especially their inhibitory activity of phosphoprotein phosphatases in cancer treatment, were discussed in this mini review, which could help to design new small molecule modulators for other biological models.